Real time security assessment in national load despatch centre, Tenaga Nasional Berhad, Malaysia - Sreedharan, G.; Moghavvemi, M. (2007)
In NLDC, the power system control centre of Tenaga Nasional Berhad, the use of on-line security assessment is still in the early stages. This paper undertakes a project implementation of a real time security assessment using VSAT and PSS/E. Real time data is obtained via NLDC's Westinghouse system in a format of different platform. The data is then converted to PTI's version 29 power flow data before it is modified to meet VSAT input data needs. The real time power flow data is then solved using PSS/E and saved. The real time data is then channeled to VSAT to conduct N-1, N-2 and Transfer Analysis of the TNB power system at an interval of 10 minute cycle. The evaluated real time scenario results are then extracted and custom made to be viewed by the system operator using Microsoft Excel. The entire security assessment process is accomplished using PSS/E, VSAT, Visual Basic programming, IPLAN and Microsoft Schedule Task.